“Role Of Guduchyadi Churna On Rajonivrutti Avastha With Special Reference To Postmenopausal Syndrome”- A Review Of Literature - Kumar, Suresh; Saini, Dholaram; Brijgopal (International Research Journal of Ayurveda & Yoga, 2021)
Menopause is defined retrospectively as the time of the Final Menstrual Period (FMP), followed by 12 months of amenorrhea. Post menopause describes the period following the final menses. In Ayurveda, this phenomenon is considered as a natural process due to aging and not associated with any serious health problems. Menopause is a state of Vata predominance & Dhatukshaya (depletion of tissue) and it occurs at the age of 50 years. The menopause is permanent cessation of menstruation at the end of reproductive life due to loss of ovarian follicular activity. The age at menopause appears to be genetically determined and is unaffected by race, socioeconomic status, age at menarche, or number of prior ovulations. Factors that are toxic to the ovary often result in an earlier age of menopause; for example, women who smoke experience an earlier menopause. Women who have had surgery on their ovaries, have had a hysterectomy, despite retention of their ovaries, may also experience early menopause. In U.K. average age for menopause is 52 (National Health Service) while in the U.S.A, it is 51 (National Institute of Aging). About 1/5th women in India experience menopause before the age in 41, but average age is 50 years and about 10% women seek medical advice during menopause. Premature ovarian failure is defined as menopause before the age of 40 years. It may be idiopathic or associated with toxic exposure, chromosomal abnormality, or autoimmune disorder. ‘Guduchyadi Churna’ drug can be effective in the management of Postmenopausal Syndrome and can be an effective, safe, promising and cost effective remedy.